(The Effect of Temperature, Duration of Heat Treatment and Potasium Hydroxide Concentration on The Transformation of eugenol Inti Iso-Eugenol Derived from Clove Leaf Oil) - Achmad Moestafa; Priyo Waspodo; Sahat P Sitorus (Warta Industri Hasil Pertanian, 1990)
Iso-eugenol is one that the compounds which is used as flavor and fragrance materials. The compounds can prepared synthetically from eugenol through a chemical reaction at certain temperature and basic concentration. It was of observed that the concentration of KOH solution and the duration of heat treatment had significantly affected the transformation of eugenol into iso-eugenol. The higher yield was found (82.88%) when eugenol was treated with 50% of KOH at 180 C for 90 minutes.